Search for rare decays of Z and Higgs bosons to J/ψ and a photon in proton-proton collisions at √s = 13 TeV - Sirunyan, A. M.; Tumasyan, A. R.; Adam, Wolfgang; Ambrogi, Federico; Asilar, Ece; Md. Ali, Mohd. Adli (Springer Nature, 2019)
A search is presented for decays of Z and Higgs bosons to a J/ψ meson and a photon, with the subsequent decay of the J/ψ to μ+μ−. The analysis uses data from proton-proton collisions with an integrated luminosity of 35.9 fb−1 at √s = 13 TeV collected with the CMS detector at the LHC. The observed limit on the Z → J/ψγ decay branching fraction, assuming that the J/ψ meson is produced unpolarized, is 1.4 × 10−6 at 95% confidence level, which corresponds to a rate higher than expected in the standard model by a factor of 15. For extreme-polarization scenarios, the observed limit changes from −13.6 to +8.6% with respect to the unpolarized scenario. The observed upper limit on the branching fraction for H → J/ψγ where the J/ψ meson is assumed to be transversely polarized is 7.6×10−4, a factor of 260 larger than the standard model prediction. The results for the Higgs boson are combined with previous data from proton-proton collisions at √s = 8 TeV to produce an observed upper limit on the branching fraction for H → J/ψγ that is a factor of 220 larger than the standard model value.